1999
DOI: 10.1002/etc.5620181023
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative assessment of genotoxicity using random amplified polymorphic DNA: Comparison of genomic template stability with key fitness parameters in Daphnia magna exposed to benzo[a]pyrene

Abstract: A method of DNA profiling using the random amplified polymorphic DNA (RAPD) was used to assess toxicant-induced DNA effects in laboratory populations of Daphnia magna exposed to varying concentrations of the genotoxic hydrocarbon benzo[a]pyrene. These effects, represented by changes in the RAPD profiles, were compared with a number of key ecological fitness parameters (age-specific survival, age-specific fecundity, net reproductive rate, and intrinsic rate of population increase). Not only was the RAPD profili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(79 citation statements)
references
References 34 publications
3
74
0
Order By: Relevance
“…GTS implies a qualitative measure reflecting changes in RAPD profiles. GTS related to the level of DNA damage, the efficiency of DNA repair and replication (Atienzar et al, 1999) could explain the appearance and disappearance of bands. The lowest values were obtained in samples no.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GTS implies a qualitative measure reflecting changes in RAPD profiles. GTS related to the level of DNA damage, the efficiency of DNA repair and replication (Atienzar et al, 1999) could explain the appearance and disappearance of bands. The lowest values were obtained in samples no.…”
Section: Resultsmentioning
confidence: 99%
“…Polymorphism observed in RAPD profiles included the disappearance of a normal band and appearance of a normal band in comparison to RAPD profiles in the control (Atienzar et al, 1999;Liu et al, 2005) and the total number of band changes is given in Table 3.…”
Section: Data Analysis For Rapd Fingerprintsmentioning
confidence: 99%
“…If left un-repaired, oxidative DNA damage can lead to detrimental biological consequences in organisms, including mutations and transformation of cells to malignant cells and cell death. Previous studies showed that changes in genomic DNA could reflect DNA alterations from single base changes (point mutations) to complex chromosomal rearrangements (Atienzar et al 1999(Atienzar et al , 2002.…”
Section: Antioxidant Activity Of D Glabra Leaves Extract (Dge) Againmentioning
confidence: 99%
“…Being a way of qualitative measurement of genotoxic effects, GTS is related to the level of DNA damage and also efficacy of DNA repair and replication (Atienzar et al 1999;Liu et al 2005;Cenkci et al 2010;Erturk et al 2012). GTS was used for comparing the changes in RAPD profiles, where generally in this study, GTS values tended to decrease with increasing concentrations of metal treatments.…”
Section: Resultsmentioning
confidence: 81%